If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + 2(5 + -4x) = 22 + -2x -6 + (5 * 2 + -4x * 2) = 22 + -2x -6 + (10 + -8x) = 22 + -2x Combine like terms: -6 + 10 = 4 4 + -8x = 22 + -2x Solving 4 + -8x = 22 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 4 + -8x + 2x = 22 + -2x + 2x Combine like terms: -8x + 2x = -6x 4 + -6x = 22 + -2x + 2x Combine like terms: -2x + 2x = 0 4 + -6x = 22 + 0 4 + -6x = 22 Add '-4' to each side of the equation. 4 + -4 + -6x = 22 + -4 Combine like terms: 4 + -4 = 0 0 + -6x = 22 + -4 -6x = 22 + -4 Combine like terms: 22 + -4 = 18 -6x = 18 Divide each side by '-6'. x = -3 Simplifying x = -3
| -6(-2x+2)+4(3+4x)=28 | | 10xt=1.8654 | | (a+6)(a^2-8a+8)=0 | | 6m^2+66m+121=0 | | 3.0=0.4m-2+0.2m | | 8w-3w-4w-1=32 | | (7y)^1/3 | | 10xt= | | 5x+10+x=-8 | | (5x+3)(2x-6)=0 | | px^2+qx+r=(x+1)(2x-7) | | 3x-2=x*x | | 3s-2s-1=29 | | 79=-7k | | 34/36 | | -29j+35j-(-39)=-33 | | (2x-2)(4x-7)=0 | | X/6-x/8=9 | | 3√7/9x2 | | 5y-8=8-4y-4 | | 12=-3(2-2r)-(2r+2) | | -2x(x^2+4x-5)=0 | | 35t-25t+10t-16t-3=49 | | 20=6x^2-7x | | x^y-^/x-4^y3^ | | 35k+7k-37k-k-3k+2=24 | | 4u+v-9u+18v= | | 3^sqrt7/9x^2 | | -26=-4(5-5n)-6(n-6) | | 43z-41z+5z=49 | | m^2+2m-7=8 | | 3u^2+u-14=0 |